Occupation classification predicts return to work after carpal tunnel decompression. (7th May 2020) - Stirling, P H C; Jenkins, P J; Clement, N D; Duckworth, A D; McEachan, J E
Abstract: Background: The relationship between hand function, employment status and return to work (RTW) after carpal tunnel decompression (CTD) is unclear. Aims: To investigate predictors of RTW following CTD. Methods: We prospectively collected pre-operative and 1-year post-operative outcomes and RTW data for all patients undergoing CTD at one centre between 29 May 2014 and 29 May 2017. We used the Standard Occupation Classification 2010. Results: Pre- and post-operative results were available for 469 (79%) of the 597 patients who had CTD surgery. Pre-operatively, 219 (47%) were employed, 216 (46%) were retired, 26 (6%) were not working due to long-term illness and eight (2%) were unemployed. Complete data sets were available for 178 (81%) of the 219 employed patients, of whom 161 (90%) were able to RTW. Of the rest, five (3%) had changed jobs and 12 (7%) were unable to work. Median RTW time was 4 weeks (interquartile range [IQR] 2–6 weeks). Significantly more patients undertaking manual labour were unable to RTW (15% versus 5%; P < 0.05). There was no significant difference in mean number of weeks absent between manual (5.7; 95% confidence interval [CI] 4.9–6.5) and non-manual workers (6.2; 95% CI 4.8–7.6) ( P > 0.05). Median pre-operative (difference 15.9; 95% CI 4.5–25) and post-operative (difference 43.2; 95% CI 13.6–43.2) hand function scores were significantly worse in patients who did not RTW ( P < 0.05). Conclusions: Most patients can RTW within 1 year of CTD. Failure to RTW is more likely in manual workers and patients with poorer pre-operative hand function.